PHYSIOLOGICAL AND BLOOD BIOCHEMICAL RESPONSES OF Pangasianodon hypophthalmus ENRICHED PELLETS Citrus jambhiri L. - Cindy Naomi Fadilla Christine Simalango; Morina Riauwaty; Henni Syawal (Asian Journal of Aquatic Sciences, 2025)
Jungga lime (Citrus jambhiri L.)/Sundai acid/Limau kuit is a natural ingredient that contains alkaloids, saponins, steroids, tannins, flavonoids, ascorbic acid, essential oils, and limonene, which are antibacterial. This research was conducted from August to December 2024 at the Laboratory of Fish Diseases and Parasites, Faculty of Fisheries and Marine, Universitas Riau. This research aimed to analyze the physiological and biochemical responses of the blood of striped catfish. The method used was experimental with a completely randomized design (CRD) of 1 factor, five treatments, and three replicates. The treatments applied were Kn (without the addition of jungga lime and without being infected with A. hydrophila), Kp (without jungga lime and infected with A. hydrophila), and jungga lime-enriched pellets at P1 (6.0 mL/kg), P2 (6.5 mL/kg), and P3 (7.0 mL/kg), and infected with A. hydrophila. Striped catfish (P. hypophthalmus) with a size of 8-12 cm and a weight of 6-7 g were kept in a 54x37x29 cm container, with a stocking density of 1 fish/3 L, and fed 3 times a day and sanitation. On day 32, fish were intramuscularly challenged with A. hydrophila (108 CFU/mL) at 0.1 mL. The results showed that the best dose was P3 (7.0 mL/kg) with a blood glucose of 79.33 mg/dL, Mg 3.07 mg/dL, Ca 9.87 mg/dL, P 4.03 mg/dl, Lisozyme activity of 259 units, mL, weight growth reached 19.11 g, and length growth reached 5.39 cm. Adding jungga lime to fish feed can improve post-challenge fish blood's physiological and biochemical responses